2014
DOI: 10.1063/1.4870233
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermodynamic properties of Fe1.12Te with multiple phase transitions

Abstract: The parent compound of iron chalcogenide superconductors, Fe1+yTe, with a range of excess Fe concentrations exhibits intriguing structural and magnetic properties. Here, the interplay of magnetic and structural properties of Fe1.12Te single crystals have been probed by low-temperature synchrotron X-ray powder diffraction, magnetization, and specific heat measurements. Thermodynamic measurements reveal two distinct phase transitions, considered unique to samples possessing excess Fe content in the range of 0.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…More detailed low‐temperature neutron as well as SXRD experiments revealed three different types of magnetic and structural behavior in Fe1+yTe depending on the amount of excess Fe . In the compositional range y<0.11, Fe1+yTe undergoes a simultaneous first‐order phase transition to a monoclinic (P21/m) as well as bicollinear antiferromagnetic phase.…”
Section: Fe1+ytementioning
confidence: 99%
“…More detailed low‐temperature neutron as well as SXRD experiments revealed three different types of magnetic and structural behavior in Fe1+yTe depending on the amount of excess Fe . In the compositional range y<0.11, Fe1+yTe undergoes a simultaneous first‐order phase transition to a monoclinic (P21/m) as well as bicollinear antiferromagnetic phase.…”
Section: Fe1+ytementioning
confidence: 99%
“…Fobes et al observed that the hysteretic transition is associated to a development of bicollinear antiferromagnetic order and a ferro-orbital ordering which results in metallic transport behaviour [8]. Here, by substitution with Se the transition temperatures are altered even though the nature of the transitions appears to be preserved [7]. While T N is decreased for x = 0.02 compared to the pristine compound, T S is increased, a behaviour which is also reflected in a reduced temperature span of the transition in the sample x = 0.02.…”
Section: Crystal Structurementioning
confidence: 99%
“…At T N ≈ 45 K, the transition in specific heat turns into a broad hump which could either be the result of two weak transitions occurring at very close temperature or of a broad transition. Similarly, for x = 0.1, a weak hump is present near 36 K. The specific heat data of samples 0.02 ≤ x ≤ 0.10 are analyzed in detail with respect to the weak transitions: The lattice contribution is modelled using a combination of Debye and Einstein models as discussed in [7]. The model is fitted to our experimental data in the range 2 K ≤ T ≤ 275 K excluding the transition regions.…”
Section: Specific Heatmentioning
confidence: 99%
See 2 more Smart Citations